2012
DOI: 10.1258/ijsa.2012.011410
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis,Mycoplasma genitaliumandUreaplasma urealyticumin clinical and non-clinical settings, Arkhangelsk Oblast, Russia

Abstract: Russia and Eastern Europe have the fastest growing HIV epidemic in the world. As sexually transmitted infections (STIs) play an important role in HIV transmission, we conducted this study to find the prevalence of three microorganisms associated with STIs in Arkhangelsk Oblast, Russia. First void urine from 1729 participants was analysed using nucleic acid amplification testing, and all participants completed a questionnaire. One hundred and twelve (6.5%) were tested positive for Chlamydia trachomatis, 67 (3.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(27 reference statements)
0
3
0
4
Order By: Relevance
“…Carne et al [16] reported that the prevalence of co-infection of UU and CT was 1.05%. In another study, first void urine was analyzed, 12.8% of 1729 participants was tested for UU and 6.5% for CT, and a significant association was found between UU and CT, and CT was associated with similar social demographics and sexual risk behaviors as UU [35] , which might suggested that UU has a possible role as an STI pathogen, that could lead the spread of other STIs. In our study, the co-infection rate of UU and CT was 4.09%, which also indicated the co-infection about the pathogens of STIs.…”
Section: Discussionmentioning
confidence: 99%
“…Carne et al [16] reported that the prevalence of co-infection of UU and CT was 1.05%. In another study, first void urine was analyzed, 12.8% of 1729 participants was tested for UU and 6.5% for CT, and a significant association was found between UU and CT, and CT was associated with similar social demographics and sexual risk behaviors as UU [35] , which might suggested that UU has a possible role as an STI pathogen, that could lead the spread of other STIs. In our study, the co-infection rate of UU and CT was 4.09%, which also indicated the co-infection about the pathogens of STIs.…”
Section: Discussionmentioning
confidence: 99%
“…Многие исследователи приписывают каркасную функцию матрикса биопленок именно данной группе химических соединений [3,19,23]. Хотя наличие пептидогликанной оболочки не характерно для данной группы микроорганизмов, некоторые штаммы U. urealyticum способны образовывать капсулы, что может быть причиной неудач при антибактериальном лечении [22,24,25].…”
Section: обзор литературыunclassified
“…Another study showed that black race, anal intercourse, and the number of sex partners correlated with asymptomatic urethritis implicating agents including Mycoplasma and Chlamydia (Gillespie et al, 2013). C. trachomatis and M. genitalium were also found to be associated with social demographics and sexual risks in a study conducted in Russia (Berle et al, 2012). M. genitalium was found to be an independent and strong risk factor for cervicitis and PID, as compared to C. trachomatis (Biartling et al, 2012).…”
Section: Introductionmentioning
confidence: 99%